2018
DOI: 10.1002/hed.25098
|View full text |Cite
|
Sign up to set email alerts
|

Thyroidectomy in patients who have undergone gastric bypass surgery

Abstract: Refractory hypocalcemia in patients who have undergone gastric bypass surgery is underreported. Careful consideration should be given to performing staged thyroidectomy and, in some cases, reversal of the bariatric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Hence, a total thyroidectomy could interfere with this compensatory process, resulting in an increased risk of postoperative primary hypoparathyroidism and hypocalcaemia [8]. Off-label treatment with teriparatide was started in our patient and resulted in stable serum calcium levels after 1 week.…”
Section: Discussionmentioning
confidence: 81%
“…Hence, a total thyroidectomy could interfere with this compensatory process, resulting in an increased risk of postoperative primary hypoparathyroidism and hypocalcaemia [8]. Off-label treatment with teriparatide was started in our patient and resulted in stable serum calcium levels after 1 week.…”
Section: Discussionmentioning
confidence: 81%
“…One possible explanation could be the malabsorption due to the modified anatomy of RYGB: the duodenum and the proximal jejunum have the highest concentration of calcium transporters, and are thus, the main absorption sites of calcium (28). After gastric bypass surgery, the food no longer passes through these portions of the bowel, resulting in calcium and vitamin D deficiencies (16,18).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported that gastric bypass patients who undergo TT have a higher rate of recalcitrant, symptomatic hypocalcemia and increased postoperative requirements of intravenous calcium, which leads to a prolonged hospital stay (15)(16)(17)(18)(19). Different strategies have been evaluated to prevent hypocalcemia in bariatric patients undergoing TT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bariatric patients who have undergone a malabsorptive operation and who later require total thyroidectomy are at additional risk for hypocalcemia. For example, RYGB has been identified as a risk factor for postoperative hypocalcemia after thyroidectomy and such management can be challenging [78,79]. Compared with patients without prior weight loss surgery, postthyroidectomy hypocalcemia in bariatric surgery patients tends to be delayed and severe, resulting in greater odds of hospitalization.…”
Section: Thyroid Cancermentioning
confidence: 99%